Current State and Future Directions of Intranasal Delivery Route for Central Nervous System Disorders: A Scientometric and Visualization Analysis - Wu, Haiyang; Zhou, Yan; Wang, Yulin; Tong, Linjian; Wang, Fanchen; Song, Sirong; Xu, Lixia; Liu, Baolong; Yan, Hua; Sun, Zhiming (Frontiers in Pharmacology, 2021)
Background: The management of various central nervous system (CNS) disorders has been challenging, due to highly compact blood-brain barrier (BBB) impedes the access of most pharmacological agents to the brain. Among multiple strategies proposed to circumvent this challenge, intranasal delivery route has sparked great interest for brain targeting in the past decades. The aim of this study was to apply scientometric method to estimate the current status and future trends of the field from a holistic perspective. Methods: All relevant publications during 1998–2020 were retrieved from the Web of Science Core Collection (SCIE, 1998-present). Two different scientometric software including VOS viewer and CiteSpace, and one online platform were used to conduct co-authorship, co-citation, and co-occurrence analysis of journals, countries, institutes, authors, references and keywords. Results: A total of 2,928 documents, including 2,456 original articles and 472 reviews, were retrieved. Our analysis revealed a significant increasing trend in the total number of scientific publications over the past 2 decades (R2 = 0.98). The United States dominated the field, reflecting in the largest amount of publications (971), the highest H-index (99), and extensive international collaboration. Jamia Hamdard contributed to most publications. Frey WH and Illum L were key researchers with the highest number of publications and citations, respectively. The International Journal of Pharmaceutics was the most influential academic journal, and Pharmacology/Pharmacy and Neurosciences/Neurology were the hottest research categories in this field. Based on keywords occurrence analysis, four main topics were identified, and the current research focus of this field has shifted from cluster 4 (pathways and mechanisms of intranasal delivery) to cluster 2 (the study of nasal drug delivery systems), especially the nanostructured and nano-sized carrier systems. Keywords burst detection revealed that the research focus on oxidative stress, drug delivery, neuroinflammation, nanostructured lipid carrier, and formulation deserves our continued attention. Conclusion: To the authors’ knowledge, this is the first scientometric analysis regarding intranasal delivery research. This study has demonstrated a comprehensive knowledge map, development landscape and future directions of intranasal delivery research, which provides a practical and valuable reference for scholars and policymakers in this field.